2011
DOI: 10.1128/aem.00180-11
|View full text |Cite
|
Sign up to set email alerts
|

High Stability of Stx2 Phage in Food and under Food-Processing Conditions

Abstract: Bacteriophages (phages) carrying Shiga toxin genes constitute a major virulence attribute in enterohemorrhagic Escherichia coli (EHEC). Several EHEC outbreaks have been linked to food. The survival of such strains in different foods has received much attention, while the fate of the mobile Shiga toxin-converting phages (Stx phages) has been less studied. We have investigated the stability of an Stx phage in several food products and examined how storage, food processing, and disinfection influence the infectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 34 publications
3
29
0
Order By: Relevance
“…Our assays, which were conducted under laboratory conditions, may or may not be the most optimal for lysogenization, since transduction under "in vivo" conditions seems to be very effective (25,26,28,29). The Stx phage induced from the Norwegian O103:H25 isolate was shown to be capable of lysogeny after storage in a dry-fermented sausage model (36).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our assays, which were conducted under laboratory conditions, may or may not be the most optimal for lysogenization, since transduction under "in vivo" conditions seems to be very effective (25,26,28,29). The Stx phage induced from the Norwegian O103:H25 isolate was shown to be capable of lysogeny after storage in a dry-fermented sausage model (36).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, both phages generate phage suspensions after induction from their lysogens with a constantly high number of phages, which allowed the replicates presented in our study. Other studies on the survival of Stx phages have been conducted using only one Stx phage of the same morphological type (36,37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that stx phages can persist longer than their host bacteria in an aquatic environment (Muniesa et al, 1999;Allué-Guardia et al, 2014). In addition, some stx phages have a high ability to tolerate exposure to certain disinfectants and can maintain their infectivity under food-processing conditions (Muniesa et al, 1999;Kajiura et al, 2001;Rode et al, 2011).…”
Section: Dissemination Of Stx Phages Outside the Intestinementioning
confidence: 99%
“…Induction of Stx2-prophages by 2.5% sodium citrate also induced Stx expression without formation of infective phage particles (39). Low pH interferes with phage infectivity by inhibition of the formation of Stx2-prophages or by inactivation of phages after correct assembly and release (40,41). Induction of Stx production without release of infectious phages may benefit E. coli in defense against predatory protozoa (35) but is not of concern for food safety.…”
Section: Discussionmentioning
confidence: 99%